Development and application of interatomic potentials to study the stability and shear strength of Ti/TiN and Cu/TiN interfaces. (November 2020) - Miraz, Abu Shama Mohammad; Dhariwal, Nisha; Meng, W.J.; Ramachandran, Bala R.; Wick, Collin D.
Abstract: A modified embedded atom method interatomic potential was developed to study semi-coherent metal/ceramic interfaces involving Cu, Ti and N. A genetic algorithm was used to fit the model parameters to the physical properties of the materials. To accurately describe interfacial interactions and shear, two-dimensional generalized stacking fault energy profiles for relevant slip systems were selected as one of the major parameterization targets for the models. The models were applied to study semi-coherent Ti(0001)/TiN(111) and Cu(111)/TiN(111) systems. Ti/TiN was stable with misfits accommodated away from the interface. Cu/TiN, in contrast, was more stable with misfits at the interface. A spiral pattern in the misfit dislocation networks was observed away from the Cu/TiN interface, similar to the metal/metal (111) semi-coherent interfaces. The theoretical shear strength calculated for Ti/TiN when the misfits were several layers away from the interface and for Cu/TiN with the misfit at the chemical interface, had reasonable agreement with experiment. Graphical abstract: Unlabelled Image Highlights: Modified embedded atom method interatomic potentials were developed to study Cu/TiN and Ti/TiN interfaces. The model was parameterized to high-fidelity γ-surfaces of the interfacial slip planes using a newly developed genetic parameterization scheme. Stable Cu/TiN and Ti/TiN interfaces with misfit dislocation networks were detected with the model. Shear strength calculated with the model for Ti/TiN and Cu/TiN agree well with the experimental results.